Evaluating TCE Degradation in a ZVI- PRB Using Compound Specific Isotope Analysis - Lojkasek-Lima, Paulo; Aravena, Ramon; Shouakar-Stash, Orfan; Frape, Shaun K.; Marchesi, Massimo; Fiorenza, Stephanie; Vogan, John (Águas Subterrâneas, 2011)
A pilot-scale zero-valent iron (ZVI) Permeable Reactive Barrier (PRB) was installed at an industrial facility to treat a chlorinated Volatile Organic Compound (VOC) plume. Groundwater multilevel monitoring wells showed a decrease in VOC concentrations where high levels of total organic carbon (TOC) have been detected. The geochemical data indicated reducing conditions in the areas where VOC reduction was observed, suggesting that biotic processes could be a major mechanism of VOC degradation. Compound- Specific Isotope Analysis (CSIA) using carbon stable isotopes were used as a complementary tool for evaluating the contribution of abiotic and biotic processes to VOC trends in the vicinity of the PRB. The isotopic data showed enriched isotope values around the PRB compared to the isotope composition of the VOC source confirming that VOC degradation is occurring along the PRB. A batch experiment was performed to evaluate the site-specific abiotic isotopic fractionation patterns. Field isotopic trends were different from those obtained during the batch experiment. These differences in isotopic trends combined with changes in VOC concentrations and redox parameters indicated that biotic processes are the predominant pathways involved in degradation of VOCs in the vicinity of the PRB.